Wing morphometrics as a tool in species identification of forensically important blow flies of Thailand - Narin Sontigun (2018)
© 2017 The Author(s). Background: Correct species identification of blow flies is a crucial step for understanding their biology, which can be used not only for designing fly control programs, but also to determine the minimum time since death. Identification techniques are usually based on morphological and molecular characters. However, the use of classical morphology requires experienced entomologists for correct identification; while molecular techniques rely on a sound laboratory expertise and remain ambiguous for certain taxa. Landmark-based geometric morphometric analysis of insect wings has been extensively applied in species identification. However, few wing morphometric analyses of blow fly species have been published. Methods: We applied a landmark-based geometric morphometric analysis of wings for species identification of 12 medically and forensically important blow fly species of Thailand. Nineteen landmarks of each right wing of 372 specimens were digitised. Variation in wing size and wing shape was analysed and evaluated for allometric effects. The latter confirmed the influence of size on the shape differences between species and sexes. Wing shape variation among genera and species were analysed using canonical variates analysis followed by a cross-validation test. Results: Wing size was not suitable for species discrimination, whereas wing shape can be a useful tool to separate taxa on both, genus and species level depending on the analysed taxa. It appeared to be highly reliable, especially for classifying Chrysomya species, but less robust for a species discrimination in the genera Lucilia and Hemipyrellia. Allometry did not affect species separation but had an impact on sexual shape dimorphism. Conclusions: A landmark-based geometric morphometric analysis of wings is a useful additional method for species discrimination. It is a simple, reliable and inexpensive method, but it can be time-consuming locating the landmarks for a large scale study and requires non-damaged wings for analysis.